Research on Multi-tooth Engagement of the Movable Sleeve Tooth Transmission - 张以都; 周有强 (Jixie chuandong)
The forces on the movable teeth inthe movable sleeve tooth transmission wasstudied,and the system of equations of engagement forces was established. By the singular value decomposition method the systemo f equations which is singular was succesfullysolved,and distributions of the engagementforces were found in the multi-tooth engagement constructIOn.’